2011
DOI: 10.1002/jsfa.4727
|View full text |Cite
|
Sign up to set email alerts
|

Rice varieties in relation to rice bread quality

Abstract: Based on volume, texture and crumb firmness ratio, Chenmaai and Goamibyeo were the most appropriate varieties for making bread. An intermediate AC and low WAI were the primary indicators of rice bread flour quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 15 publications
(17 reference statements)
4
43
1
2
Order By: Relevance
“…Indica rice cake and wheat cake performed the similar values of specific volume and which were significantly higher than the other two rice cakes. A similar results were concluded by Nakamura, Suzuki, andOhtsubo (2009) andHan, Cho, Kang, andKoh (2011) on the investigation of rice substituted bread. Perdon and Juliano (1975) addressed that rice of 20e25% amylose content was suitable to prepare the fermented rice cake, which got a higher specific volume than the cake made by the rice with lower or higher amylose contents.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…Indica rice cake and wheat cake performed the similar values of specific volume and which were significantly higher than the other two rice cakes. A similar results were concluded by Nakamura, Suzuki, andOhtsubo (2009) andHan, Cho, Kang, andKoh (2011) on the investigation of rice substituted bread. Perdon and Juliano (1975) addressed that rice of 20e25% amylose content was suitable to prepare the fermented rice cake, which got a higher specific volume than the cake made by the rice with lower or higher amylose contents.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…Texture or consistency of dough depends on water absorption leading to body thickening and viscosity (Aguilera et al 2011). High water absorption reduces stickiness and produces stiff dough (Han et al 2012). At bread level, Han et al (2012) found that rice lines with low water absorption produce fresh bread with a suitable volume and firmness.…”
Section: Flour and Flour Gel Hydration Propertiesmentioning
confidence: 99%
“…High water absorption reduces stickiness and produces stiff dough (Han et al 2012). At bread level, Han et al (2012) found that rice lines with low water absorption produce fresh bread with a suitable volume and firmness. Presumably, that effect could explain texture improvement observed when partial replacement of wheat flour with germinated rice and pregerminated rice (Charoenthaikij et al 2010b;Watanabe et al 2004).…”
Section: Flour and Flour Gel Hydration Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, rice flour presents technological limitations in breadmaking due to the poor functional properties of its proteins (Kadan and others ; Hager and others ). Therefore, different additives like hydrocolloids, proteins, enzymes, and emulsifiers have been used to improve volume, texture, appearance, acceptance, and shelf life of rice breads (Nishita and others ; Ylimaki and others ; Gujral and others , ; Gujral and Rosell ; Demirkesen and others ; Han and others ). Rice‐based ingredients, such as brown rice flour (Renzetti and others ), defatted rice bran (Kadan and others ), or extruded rice flour (Clerici and others ) are also used.…”
Section: Oat and Wheat Starchmentioning
confidence: 99%